Health Risk Assessment of Nitrate Exposure Originating from Gravity Feed System (GFS) Water: A Cross-Sectional Study in Hulu Langat, Selangor State, Malaysia - Muhammad Syafiq MY; Shaharuddin Shaharuddin; Retno Andriyani (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2025)
Background: This cross-sectional study assessed the health risks of nitrate exposure from the Gravity Feed System (GFS) water in Hulu Langat, Selangor state. Method: The study population consisted of 88 individuals aged 18 and older who have resided in 20th mile Village, Sungai Lui, Hulu Langat, for a long time and used GFS as their primary drinking water source. Results: The mean and standard deviation of nitrate concentration in 35 water samples were 2.49 ± 1.26 mg/L, which is well below the Malaysian National Standard for Drinking Water Quality (NSDWQ) maximum contaminant limit (MCL) of 10.00 mg/L. The mean pH of the water samples was 7.07 ± 0.28, which falls within the recommended range of 6.50 to 8.50 from the World Health Organisation (WHO). The study's Hazard Quotient (HQ) analysis showed a mean of 0.0084 ± 0.0060, with all respondents having an HQ below one, indicating no significant non-carcinogenic health risk from nitrate content in the water. The study found no significant correlation between nitrate concentrations and pH levels. Conclusion: These findings suggest that the GFS water in the study area is safe for consumption in terms of nitrate levels, although continuous monitoring is recommended.